2009
DOI: 10.2337/dc08-2077
|View full text |Cite
|
Sign up to set email alerts
|

Fetuses of Obese Mothers Develop Insulin Resistance in Utero

Abstract: OBJECTIVEOffspring of obese mothers have an increased risk for obesity and diabetes. The purpose of this study was to determine whether fetuses of obese women have increased obesity, insulin resistance, and markers of inflammation, supporting the concept of fetal programming.RESEARCH DESIGN AND METHODSFifty-three lean and 68 obese women with singleton term pregnancies were evaluated at elective cesarean delivery. Maternal and umbilical cord blood was obtained for measures of insulin resistance and cytokines. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
444
9
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(516 citation statements)
references
References 25 publications
(32 reference statements)
42
444
9
9
Order By: Relevance
“…22 The underlying mechanisms by which such factors interact with each other seem quite complex because of the interaction between some factors and the possibility of intergenerational effects. 34 Some of the significant factors associated with an increased placental and birth weight that were identified in this study include high maternal early-pregnancy BMI, maternal pregnancy weight gain, higher parity, older gestational age and higher placental and birth weight, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The underlying mechanisms by which such factors interact with each other seem quite complex because of the interaction between some factors and the possibility of intergenerational effects. 34 Some of the significant factors associated with an increased placental and birth weight that were identified in this study include high maternal early-pregnancy BMI, maternal pregnancy weight gain, higher parity, older gestational age and higher placental and birth weight, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Second, we were unable to adjust for maternal glucose tolerance levels and physical activity levels, which have been associated with maternal and subsequent child adiposity levels. 22,23 Recent studies have shown that women, who are overweight or obese before pregnancy, have a marked decrease in insulin sensitivity during pregnancy resulting in a greater availability of lipids and glucose for the fetus. 24,25 At birth, such babies have higher cord concentrations of insulin and leptin and tend to have a higher fat mass.…”
Section: Discussionmentioning
confidence: 99%
“…Body composition of the mother during gestation may affect offspring development. In humans, babies born from obese mothers have increased body fat percentage, higher rates of diabetes and higher rates of insulin resistance (Hull et al, 2008;Catalano et al, 2009). However, little is known about maternal feed level and body condition interactions during pregnancy and how they influence offspring growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…While this could be the result of shared genetic predisposition and a similar lifestyle, there is now increasing evidence suggesting that an obesogenic uterine environment is of major importance in modulating long-term risk of adiposity and related outcomes. This evidence includes several reports that suggest that children of obese mothers have a higher risk of obesity than children of obese fathers (22)(23)(24) . Also, children born to formerly obese women who had undergone bariatric surgery leading to weight loss, had only half the risk of becoming obese as compared with their older brothers and sisters who had been born prior to bariatric surgery and hence under a less favourable prenatal metabolic and endocrine environment (25) .…”
Section: Fuel-mediated In Utero Hypothesismentioning
confidence: 99%